2004
DOI: 10.1002/jcp.20188
|View full text |Cite
|
Sign up to set email alerts
|

Developmental transcription factor slug is required for effective re‐epithelialization by adult keratinocytes

Abstract: Taken together, these findings suggest that Slug plays an important role during wound re-epithelialization in adult skin and indicate that Slug controls some aspects of epithleial cell behavior in adult tissues as well as during embryonic development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
199
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(217 citation statements)
references
References 39 publications
15
199
2
1
Order By: Relevance
“…Nevertheless, a significant decrease of MMP9 and mesenchymal markers was detected in CarB-shSnai2 xenografts (Figure 5), suggesting that Snai2 can control certain aspects of tumor invasion/differentiation in determined tumor contexts. These observations are also compatible with the differential roles proposed for Snai1 and Snai2 factors in individual vs collective tumor invasion, or distinct anatomic dissemination of breast and ovarian tumors (Elloul et al, 2005(Elloul et al, , 2006Come et al, 2006), and for Snai2 in wound healing migration (Savagner et al, 2005).…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, a significant decrease of MMP9 and mesenchymal markers was detected in CarB-shSnai2 xenografts (Figure 5), suggesting that Snai2 can control certain aspects of tumor invasion/differentiation in determined tumor contexts. These observations are also compatible with the differential roles proposed for Snai1 and Snai2 factors in individual vs collective tumor invasion, or distinct anatomic dissemination of breast and ovarian tumors (Elloul et al, 2005(Elloul et al, , 2006Come et al, 2006), and for Snai2 in wound healing migration (Savagner et al, 2005).…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, dissociation of E-cadherin-mediated junctions can lead to autoregulatory induction of Slug and subsequent repression of E-cadherin transcription (Conacci-Sorrell et al, 2003). A role for Slug was also proposed in EMT associated with re-epitelization of cutaneous wounds, while Snail was not involved (Savagner et al, 2005), consistent with differential expression of these genes observed in TGFb-induced EMT in keratinocytes, renal tubular epithelial cells, and mammary epithelial cells (Zavadil et al, 2004).…”
Section: Snail/slugmentioning
confidence: 76%
“…They regulate cell migration, left-right symmetry, stem cell survival, and epithelial-to-mesenchymal transitions (EMT) during metazoan development (Barrallo-Gimeno and Nieto, 2005;Boyer et al, 2000;Nieto, 2002), as well as dedifferentiation and regeneration in the mature adult (Savagner et al, 2005;Zhao et al, 2002). Members of this family, particularly Snail1 and Snail2, function primarily as repressors of gene transcription, regulating a variety of epithelial-specific genes involved in cell adhesion and epithelial cell identity (Bolos et al, 2003;Kajita et al, 2004;Tripathi et al, 2005).…”
Section: Resultsmentioning
confidence: 99%